Where credit is due : how Africa's debt can be a benefit, not a burden - Smith, Gregory (London Hurst and Company, 2021)
African countries are seeking calmer capital, to raise living standards and give their economies a competitive edge. The African debt landscape has changed radically in the first two decades of the twenty-first century. Since the clean slate of extensive debt relief, states have sought new borrowing opportunities from international capital markets and emerging global powers like China. The new debt composition has increased risk, exacerbated by the 2020 coronavirus pandemic: richer countries borrowed at rock-bottom interest rates, while Africa faced an expensive jump in indebtedness.
Includes index
Keywords: Africa, Debt